2014
DOI: 10.1055/s-0034-1375666
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Bone, Fat Tissue and Metabolic Control in Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Our data suggest significant relationships between bone, fat tissue and glucose metabolism in pediatric patients with T1DM. The results can confirm that poor metabolic control is associated with reduced bone formation. On the other hand fat and bone tissue can influence glucose metabolism, potentiality in insulin-dependent manner. From these data leptin or OC may be potentially used as additional therapeutic agents for T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…This was further reinforced by the lower levels of CTX, a marker of bone resorption, in the T1DM cases. This state of low bone turnover with reduced bone formation in T1DM has been reported previously and has been known to be associated with GH deficiency . To facilitate recruitment, the current study did not stipulate fasting blood samples.…”
Section: Discussionmentioning
confidence: 87%
“…This was further reinforced by the lower levels of CTX, a marker of bone resorption, in the T1DM cases. This state of low bone turnover with reduced bone formation in T1DM has been reported previously and has been known to be associated with GH deficiency . To facilitate recruitment, the current study did not stipulate fasting blood samples.…”
Section: Discussionmentioning
confidence: 87%
“…By and large, most published clinical studies have reported a correlation between osteocalcin circulating levels and glucose homeostasis in humans as well [29][30][31][32][33][34][35][36][37][38][39][40]. These studies, because of their correlative nature, had to be interpreted cautiously and needed a more direct confirmation; this came once the osteocalcin receptor had been identified.…”
Section: Identification Of Gprc6a As An Osteocalcin Receptor In Mice mentioning
confidence: 99%
“…The possible contribution of osteocalcin to reduced BMD in T1DM was tested in several studies, mostly using adult patients. In a study of 78 patients aged 11.5±4.3 years with T1DM and 11 controls, serum osteocalcin negatively correlated with HbA1c levels (65). In that study osteocalcin also negatively correlated with leptin, which reflects body adiposity.…”
Section: Introductionmentioning
confidence: 99%